Psoriasis Patients' Knowledge about the Disease and Treatments - Astrid Klopstad Wahl; Torbjørn Moum; Hilde Stendal Robinson; Eva Langeland; Marie Hamilton Larsen; Anne Lene Krogstad (Hindawi Limited, 2013)
Patients' knowledge about psoriasis and its treatment has been randomly studied previously. The aim of the study is to investigate patients' knowledge about psoriasis in relation to undergoing patient education in the context of climate therapy (CT). The psoriasis knowledge questionnaire (PKQ) was used in a follow-up pre-post study design of Norwegian patients with psoriasis at the age of 20 years and older undergoing CT at Gran Canaria (Spain). Patients completed the PKQ and provided selected demographic, clinical and health information before (T1), immediately after (T2), and 3 months after (T3) CT. Disease severity was assessed using the psoriasis area and severity index (PASI). 254 psoriasis patients were included (74%). The PKQ score improved significantly from T1 to T2 and T3 (P<0.001 for both comparisons). Although patient's knowledge improved, further research should use gold standard designs (experiments) to study the effects of educational interventions in different contexts.